Inhibiting creep in fine-grained MgAl alloys through grain boundary stabilization - Lingbao Ren; Yurong Zhao; Jinjin Li; Fei Liu; Boyu Liu; Ge Wu; Carl J. Boehlert; Zhiwei Shan (Journal of Magnesium and Alloys)
The limited creep resistance of wrought MgAl alloys restricts their lightweight applications at intermediate temperatures due to the softening effect of discontinuous precipitation (DP) on the dislocation-controlled creep. Here, we developed a creep-resistant wrought MgAl alloy through microalloying of Y and Ca. The resulting alloy exhibited an order of magnitude enhancement in the creep resistance at 125 ℃/50–100 MPa. In contrast to the grain boundary instabilities by DP in the previously reported wrought MgAl alloys, we show that the addition of 0.21Y+0.15Ca wt% produces a (Zn+Ca) co-segregation at the grain boundaries as a result of their segregation energy and the activation energy of grain boundary migration, thereby stabilizing the grain boundaries. The (Zn+Ca) co-segregation inhibits the dynamic DP and promotes the formation of intragranular Al-enriched clusters, which favorthe formation of Al2Y, Mg17Al12 nano precipitates, thereby impeding intragranular dislocation motion during creep. Furthermore, the addition of 0.21Y+0.15Ca wt% facilitates the formation of a fine and uniform recrystallization structure in the microalloyed alloys compared to AZ80 due to the high activation energy of mobility for the (Zn+Ca) segregated grain boundary. Therefore, the microalloyed alloys exhibit good tensile properties with 380 MPa tensile strength and 18% elongation. Our constitutive analysis revealed that the (Y+Ca) microalloying decreased the creep stress exponent by 29% and increased the creep resistance in the medium to high-stress range. Microalloying provides a promising way to develop low-cost creep-resistant wrought MgAl alloys.